2021
DOI: 10.1007/s40266-021-00852-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Association of Nimodipine and Choline Alphoscerate in the Treatment of Cognitive Impairment in Patients with Cerebral Small Vessel Disease. The CONIVaD Trial

Abstract: Background No approved treatment is available for patients with vascular cognitive impairment (VCI) due to cerebral small vessel disease (SVD). Objective The CONIVaD (Choline Alphoscerate and Nimodipine in Vascular Dementia) study aimed to investigate the feasibility, efficacy, and safety of a combined treatment with choline alphoscerate and nimodipine in patients with SVD and mild-to-moderate cognitive impairment. Methods Within this pilot, single-center (university hospital), double-blinded, randomized clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…It is highly lipid-soluble, and it easily crosses the blood-brain barrier, resulting in better distribution of its bioactive form in the intracranial tissues than other calcium antagonists, as well as enhanced effect in the perivascular region of the brain. Previous research has shown that nimodipine produced significant differences between pre-and posttreatment temporal orientation, memory, calculation, and decision-making parameters in patients with mild PSCI, before and after treatment [17]. Cochrane used nimodipine at a dose of 90 mg/day for 12 -24 weeks, produced a 39 % reduction in cognitive decline, with significant improvements in memory, attentiveness, orientation, and mood swings, thereby providing a rationale for the use of the drug [18].…”
Section: Discussionmentioning
confidence: 95%
“…It is highly lipid-soluble, and it easily crosses the blood-brain barrier, resulting in better distribution of its bioactive form in the intracranial tissues than other calcium antagonists, as well as enhanced effect in the perivascular region of the brain. Previous research has shown that nimodipine produced significant differences between pre-and posttreatment temporal orientation, memory, calculation, and decision-making parameters in patients with mild PSCI, before and after treatment [17]. Cochrane used nimodipine at a dose of 90 mg/day for 12 -24 weeks, produced a 39 % reduction in cognitive decline, with significant improvements in memory, attentiveness, orientation, and mood swings, thereby providing a rationale for the use of the drug [18].…”
Section: Discussionmentioning
confidence: 95%
“…All of the included studies (eight studies) were 278 conducted between 1993 and 2022 in Russia (one 279 study) [29], Italy (six studies) [30][31][32][33][34][35], and Mexico (one study) [36] (Table 1). In four RCTs, ␣-GPC was combined with the cholinesterase inhibitor (ChE-I) donepezil [30,31,33,35].…”
Section: Study Characteristics 277mentioning
confidence: 99%
“…In four RCTs, ␣-GPC was combined with the cholinesterase inhibitor (ChE-I) donepezil [30,31,33,35]. In one RCT, ␣-GPC was evaluated in combination with nimodipine [34], and the effects of ␣-GPC were examined in three RCTs without any combination of treatments [29,32,36].…”
Section: Study Characteristics 277mentioning
confidence: 99%
See 1 more Smart Citation
“…GPC, a choline precursor, increases and releases acetylcholine (ACh) to enhance cholinergic transmission [ 8 , 9 , 10 ]. Since GPC is well tolerated with adequate central nervous system penetration [ 11 ], recent investigations have proved that GPC has some positive effects on cognitive improvement in various clinical settings [ 12 , 13 ]. Although the guideline for the pharmacological approach has not been established, many neuro-oncologists have worried about the decline of cognitive function caused by treatments or disease progression and prescribed several drugs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%